2007
DOI: 10.1007/s11090-007-9085-z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of UV light to the decomposition of toluene in dielectric barrier discharge plasma/photocatalysis system

Abstract: The contribution of UV light from plasma and an external UV lamp to the decomposition of toluene in a dielectric barrier discharge (DBD) plasma/UV system, as well as in a plasma/photocatalysis system was investigated. It was found that UV light from the DBD reactor was very weak. Its contribution to the removal of toluene in the plasma/photocatalysis system could be ignored. Whereas, the introduction of external UV light to the plasma significantly improves the removal efficiency of toluene by 20%. The removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 16 publications
2
26
0
Order By: Relevance
“…This observation was supported by the work of Cal and Schluep [38], that studied two different gap distances (3 and 5 mm) between electrodes and observed that the reactor with the 5 mm gap spacing required about three times the amount of power compared to the reactor with the 3 mm gap to achieve a benzene RE of 95%. the RE of isovaleraldehyde, also seen for similar catalysts elsewhere [39]. These results…”
Section: Dielectric Barrier Discharge Reactor 321 Effects Of Inlet supporting
confidence: 81%
“…This observation was supported by the work of Cal and Schluep [38], that studied two different gap distances (3 and 5 mm) between electrodes and observed that the reactor with the 5 mm gap spacing required about three times the amount of power compared to the reactor with the 3 mm gap to achieve a benzene RE of 95%. the RE of isovaleraldehyde, also seen for similar catalysts elsewhere [39]. These results…”
Section: Dielectric Barrier Discharge Reactor 321 Effects Of Inlet supporting
confidence: 81%
“…Comparison of these two design parameters clearly indicates the potential of PDC process for the VOC removal. Recent studies, however, provided several experimental evidences that the role of UV in the PDC process is minor due to the low UV dose [45,46]. UV dose in photocatalytic process is in the order of several mW cm −2 , whereas it is only in the order of several μW cm −2 in nonthermal plasma in air.…”
Section: -P9mentioning
confidence: 99%
“…Several studies suggested that photocatalysis using ozone-generating short-wavelength UV light [16][17][18][19][20] or in combination with atmospheric non-thermal plasma [21][22][23][24] can be suitable alternatives for indoor air cleaning. These radiation sources present the additional advantage of generating excess ozone, as well as other potentially harmful, reactive species that should be prevented from being introduced into occupied spaces.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of toluene due to this reaction is likely similar to the short reactor residence time. Due to the generation of ozone in this process, photocatalytic oxidation under 185 + 254 nm is often termed UV/TiO 2 /O 3 [17,[18][19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation